Peran Pelatihan Public Speaking Dalam Menumbuhkan Rasa Percaya Diri Siswa - Ambarsari, Dewi; Putri, Martina Shalaty (LUGAS Jurnal Komunikasi, 2024)
Communication is a key factor in the effective delivery of messages. Therefore,every individual must possess the ability to communicate effectively and efficiently.Public speaking is one form of effective communication that requires specificskills. A lack of communication skills can hinder an individual's confidence whenspeaking in public. Public speaking is often called "pidato" (speech) in Indonesian.A speech involves delivering ideas or thoughts to an audience using clear, polite,and understandable language. The ability to speak in public should be cultivatedfrom an early age, especially during schooling, so that students develop confidencein expressing their opinions. Self-confidence is the belief in one’s abilities,enabling individuals to remain unaffected by the opinions of others and to act inalignment with their desires while maintaining happiness, optimism, tolerance, andresponsibility. The purpose of this study is to examine the role of public speakingtraining in fostering self-confidence among students, particularly those at SMAN 7Bekasi who have participated in public speaking training. This research employs aqualitative approach and is based on field research. Data were gathered throughdirect observation, in-depth interviews, and documentation analysis of books andjournals relevant to the topic. The research was conducted between March andMay 2024. The findings of this study indicate that public speaking training plays asignificant role in enhancing students' self-confidence. This is evident from thepositive changes reported by students after attending the training, includingincreased courage to speak in front of an audience, reduced fear, and a noticeableboost in self-confidence